Formation of Professional Competences of Future Specialists in 'Tourism' in the Course of Studying the Discipline "Market of Tourist Services" - Olena Binytska (Kazimierz Wielki University, 2024)
Our research examines the approaches to the formation of professional competencies of future specialists in the speciality "Tourism" in the process of studying the discipline "Market of Tourist Services". It is emphasised that the modern training of future specialists in the speciality "Tourism" should meet global standards and market needs, providing graduates with not only theoretical knowledge, but also practical skills and the ability to work in an innovative environment. As part of the "Tourism Services Market" discipline, students are offered interactive learning methods such as role-playing games, business simulations, and group projects. This contributes to the development of important skills, including marketing, organisation of travel services and communication with clients. Particular attention is paid to the study of modern digital technologies used in the tourism sector, as well as marketing approaches that help to adapt tourism products to the individual needs of consumers.